The Role of Alumni Units in Building Professional Networks for Alumni - Riqzat Liberno; Heriyanto; Trisninawati; Andrian Noviardy; Efan Elpanso (Marcha Institute, 2026)
Universities are responsible not only for producing academically competent graduates but also for preparing alumni to adapt and compete in the workplace through the development of professional networks. In this context, the alumni unit plays a strategic role as a liaison between alumni, the institution, and the industrial world. This study aims to analyze the role of the alumni unit in building professional networks for alumni, identify obstacles faced, and examine efforts made to overcome these obstacles. The study used a qualitative descriptive approach with the Alumni Unit of Bina Darma University as the research object. Data collection was conducted through observation, interviews, and documentation during internships, then analyzed descriptively to obtain an in-depth overview of alumni management. The results show that the Alumni Unit plays a role as a communication liaison between alumni and the university, a provider of career information, and a facilitator in the development of professional networks through alumni database management programs, tracer studies, seminars, webinars, and other alumni activities. The main obstacles faced include low alumni participation, alumni data that is not always up-to-date, and the wide distribution of alumni. This study concludes that the role of the alumni unit has been running well, but digital technology-based program innovation and more adaptive management strategies are needed to increase the effectiveness of the development of the alumni professional network in a sustainable manner.